2011
DOI: 10.1139/v10-154
|View full text |Cite
|
Sign up to set email alerts
|

The use of a silica-based heat sink to “uncouple” the matrix-assisted laser desorption/ionization (MALDI) mechanism

Abstract: The relationships between ion yield(s) as a function of desorption alone and (or) ionization was investigated using two model systems. In the first model system, a carbohydrate (2,3,6-tri-O-methyl-b-cyclodextrin, TMBCD), which could be directly laser desorbed, was analyzed with and without a silicon-based heat sink compound (HSC). The HSC allowed heat to pass through but obstructed the flow of charge. In the second model system, a peptide (substance P), which ccould not be laser desorbed, was analyzed under si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…As shown by our observation above, the silane shell prevents the fragmentation of MNP and functions as a “thermal sink”. 38 On the other hand, the presence of matrix (DHB) molecules augments the ability of the nanoparticles to mediate the energy transfer process and the spontaneous dissociation at high concentration. These properties afford simultaneous ionization and product ion generation, which is not feasible with the free matrix alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by our observation above, the silane shell prevents the fragmentation of MNP and functions as a “thermal sink”. 38 On the other hand, the presence of matrix (DHB) molecules augments the ability of the nanoparticles to mediate the energy transfer process and the spontaneous dissociation at high concentration. These properties afford simultaneous ionization and product ion generation, which is not feasible with the free matrix alone (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ion yields from β‐CD under either system of heat conductivity were found to be similar, whereas the ion yield of the peptide with the heat sink was negligible. It was concluded that compounds that are predominately cationized either in the gas phase or preformed in solution give an ion yield that is not dependent upon the surface conditions, whereas compounds that are not usually cationized are affected by the emission of electrons from the metal surface (Lourantos et al, ).…”
Section: Theorymentioning
confidence: 99%